Organizational Justice and Leadership Style on Employee Job Satisfaction (Empirical Study on Bappeda of West Papua Province) - Pamella Ruth Baransano; Yunus Tekad Kurniadi Ruslak Hammar (Jurnal Indonesia Sosial Teknologi, 2024)
This research aims to analyze the influence of organizational justice and leadership style on employee job satisfaction (Empirical Study at the Regional Development Planning Agency (BAPPEDA) of West Papua Province). The results of the research show that organizational justice and leadership style have a positive and significant effect on employee job satisfaction at the Regional Development Planning Agency of West Papua Province. Leadership style has a positive and significant effect on employee job satisfaction at the Regional Development Planning Agency of West Papua Province. Organizational Justice and Leadership Style simultaneously have a significant influence on the job satisfaction of employees of the Regional Development Planning Agency of West Papua Province.